Is the Prevalence of Focal and Segmental Glomerulosclerosis Increasing in the Province of Khuzestan? - Seyed Seifollah Beladi Mousavi; Fatemeh Hayati; Heshmatollah Shahbazian (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background & Objective: There is evidence that focal segmental glomerulosclerosis (FSGS) has become an important cause of adult primary nephrotic syndrome (PNS) in the USA and many other countries and the aim of this study was to evaluate this issue in the province of Khuzestan, Iran.Subjects and Methods: In a cross sectional and prospective study from January 1998 to September 2012, all the patients with PNS who referred to Imam Khomeini hospital of Ahwaz, Iran were evaluated. Renal biopsy was done by nephrologists and the biopsy samples were analyzed by light microscopy.Results: 148 patients (53 male and 39 female, mean age 51±33years) were included. Mean serum creatinine and a median rate of urinary protein excretion were 1.39mg/dl and 6450mg/day respectively. The most common histological finding was focal and segmental glomerular sclerosis (FSGS) 49 patients ,33.10%, followed by membranous glomerulonephritis (MGN) 42 patients, 28.37%, minimal change disease (MCD) 18 patients ,12.16% , membranoproliferative glomerulonephritis (MPGN) 13 patients, 8.78% , IgA nephropathy 10 patients ,6.75%, focal and segmental glomerulonephritis (FSGN) 6 patients, 4.05%, mesangial proliferative glomerulonephritis 5 patients,3.37% and diffuse proliferative glomerulonephritis 5 patients 3.37%. Conclusion: Consistent with several other countries, FSGS is the most common cause of adult primary nephrotic syndrome in Khuzestan province, Iran.